A Case Report on Management of Non-alcoholic Grade 2 Fatty Liver WSR Yakrit Vikara through Ayurvedic Intervention - kumar, Durgesh; bihari trivedi , Atal; kumar , S.S. Mohan (International Research Journal of Ayurveda & Yoga, 2025)
One of the most prevalent liver conditions in the world, fatty liver, is typically brought on by lipid build-up, primarily triglycerides in hepatocytes. Although the liver naturally contains fat, fatty liver can develop if the amount of fat exceeds 5–10% of the liver’s total weight. Yakrit (liver) is considered as a crucial organ responsible for digestion, metabolism, detoxification in body. In Ayurveda non-alcoholic grade 2 fatty liver disease can be related with Yakrit Vikara primarily caused by imbalance of Pitta Dosha leading to conditions such as jaundice, fatty liver, liver cirrhosis and hepatitis etc. this case study examines the clinical presentation, diagnosis and treatment of a male patient aged 60 years with complaint of gaseous abdomen, increased body weight, pain in right side of abdomen, and incomplete bowel evacuation since last 2 months. Diagnostic ultrasound report confirmed grade 2 fatty liver in both lobes.